Pearson Correlation Between Education Level and Population Growth on Poverty in Central Java, 2019-2021 - Bagas Dwi Cahyo; Anggi Sasmita Setyowati; Agung Prabowo (Research Collaboration Community (RCC), 2022)
Poverty is still an issue for Indonesians. In Indonesia, several provinces still have poverty rates above 10%. Central Java is one of them. The human development index (HDI), the quality of education, the minimum salary, and population growth are all factors that contribute to the unemployment rate and poverty. During the years 2019–2021, the study aims to understand the relationship or correlation between education and population increase in poverty in central Java province. We acquired a value of r of as much as -0,648 for education level and a value of r of as much as 0.335 for population growth based on the analysis of using Pearson’s correlation. The findings indicate that the level of education is strongly related to the level of poverty, whereas the relationship between population growth and poverty is weak. A negative value at r shows the relation, which is inversely. Based on the results of this study, it is also expected for the government to develop programs to improve the quality of education of its resident.